A STUDY OF BLOOD GROUP IN COVID-19 PATIENTS IN TERTIARY CARE HOSPITAL OF AHMEDABAD CITY, GUJARAT, INDIA - AN INSTITUTIONAL STUDY - Arpit Chelabhai Prajapati; Madhur Yogendra Modi; Mansi Maulik Patel; Hardik Jashubhai Sutariya; Mishal Bhavin Mody (The Indonesian Journal of Public Health, 2022)
Introduction: The associations between ABO system of blood and COVID-19 infection in various studies provide reason to think true associations may be in reality between blood type and incidence of COVID-19 and death due to COVID-19. Objectives:  To estimate frequency of COVID-19 illness in different ABO blood systems and also to find linkage between the ABO system of blood and degree of COVID-19 illness. Methods: A prospective cohort study was conducted on all COVID-19 patients (Patients were grouped A positive and A negative blood groups into 1st group and other blood types such as B, AB, and O, irrespective of their Rh status, into 2nd group) admitted at Tertiary Care Hospital of Ahmedabad City, Gujarat, India during the four months of study duration. Results: COVID-19 infection was found in 380 (63.3%) male. Mean age was 56.46 ±15.35 years in which 26.8% patients were in age group of 60 to 70 years. Among total 600 patients, 35% of patients were having B positive type of blood followed by O positive type of blood (25%). There were 25% of patients having overall co-morbidity like diabetes. And 8% of B positive patient having co-morbidity and amongst the, 1.2% patients were admitted to Intensive Care Unit. Case fatality rate was 7.5%. Among B positive blood group patients, 37.8% deaths occurred. Conclusion: Patients having blood group O may have lower chances of ICU admission as compared to other blood groups.